2018
DOI: 10.1016/j.neuron.2018.08.003
|View full text |Cite
|
Sign up to set email alerts
|

An Afferent Neuropeptide System Transmits Mechanosensory Signals Triggering Sensitization and Arousal in C. elegans

Abstract: SummarySensitization is a simple form of behavioral plasticity by which an initial stimulus, often signaling danger, leads to increased responsiveness to subsequent stimuli. Cross-modal sensitization is an important feature of arousal in many organisms, yet its molecular and neural mechanisms are incompletely understood. Here we show that in C. elegans, aversive mechanical stimuli lead to both enhanced locomotor activity and sensitization of aversive chemosensory pathways. Both locomotor arousal and cross-moda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 85 publications
2
59
0
Order By: Relevance
“…We next tested if SEB-3 and NLP-49 regulate another aspect of locomotion: touch-evoked arousal. When animals are exposed to a non-localized mechanosensory stimulus, they undergo a transient increase in locomotor activity that persists for 1–2 min [ 37 ]. To determine whether this behaviour is affected by nlp-49 and seb-3 , five taps were rapidly delivered to the Petri dish housing the animals and the speed of these animals was recorded using automated tracking software [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We next tested if SEB-3 and NLP-49 regulate another aspect of locomotion: touch-evoked arousal. When animals are exposed to a non-localized mechanosensory stimulus, they undergo a transient increase in locomotor activity that persists for 1–2 min [ 37 ]. To determine whether this behaviour is affected by nlp-49 and seb-3 , five taps were rapidly delivered to the Petri dish housing the animals and the speed of these animals was recorded using automated tracking software [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…AVK has not previously been implicated in the control of locomotion; indeed a different neuropeptide that controls arousal-like behaviour, PDF-1, appears to act primarily in a different set of neurons, AIY and ASK [ 49 , 50 ]. Interestingly, we have found that the receptor (FRPR-3) for another neuropeptide (FLP-20) required for arousal in response to mechanosensory signals is also expressed in AVK [ 37 ], suggesting that multiple neuropeptide systems may function together to promote arousal.…”
Section: Discussionmentioning
confidence: 99%
“…But when the concentration of food odors decreases, they transition to dwelling states ( Ji et al 2020 ). Detection of additional chemosensory cues also impacts these states: pheromones that signal a higher density of animals inhibit roaming ( Greene et al 2016 ), and aversive stimuli that signal potential harm can drive a high-speed state reminiscent of roaming ( Ardiel et al 2017 ; Chew et al 2018 ). These studies suggest that regulation of roaming and dwelling states depends on an integration of diverse chemosensory cues.…”
Section: Locomotion Statesmentioning
confidence: 99%
“…Each of these neurons receives additional inputs and releases neuropeptides that also influence movement. For example, the RID premotor neuron that drives forward locomotion ( Lim et al 2016 ) receives FLP-20 peptidergic inputs from sensory neurons that drive high-speed locomotion ( Chew et al 2018 ). The AIY interneuron releases multiple neuropeptides, including FLP-1 , which modulates locomotion ( Buntschuh et al 2018 ).…”
Section: Locomotion Statesmentioning
confidence: 99%
“…Each state can last up to tens of minutes and the transitions between states are abrupt. The fraction of time an animal spends in each state is influenced by its satiety, ingestion of bacterial food, and sensory cues such as odors 23,25,26 . Consistent with the notion that these states reflect an explorationexploitation tradeoff, animals favor dwelling in food-rich environments and after starvation, but favor roaming in poor-quality food environments and after aversive stimulation.…”
Section: Introductionmentioning
confidence: 99%